THE IMPACT OF MUTUAL FUND PERFORMANCE ON MUTUAL FUND MARKET VALUE WITH INTERNET FINANCIAL REPORTING (IFR) AS INTERVENING VARIABLE - Amanda Dwiluthfia Joanna (Jurnal Ilmiah Ekonomi Bisnis, 2017)
Every investor would expect a big profit from their investments. However, big profit from the investment must be accompanied by the greater risk. In determining the choice of investment in mutual fund, investor must make an assessment of its performance despite there is no certainty that a good fund performance will equal past performance of mutual funds in the future. This research aims to analyze the effect of mutual fund performance on the Internet Financial Reporting (IFR) and its market value. This research used all sharia equity mutual funds that active in 2014 as the sample. The sampling technique used is purposive sampling and get 14 mutual funds as samples. Data analysis is performed by using path analysis which is a straightforward extension of multiple regressions and Kendall of concordance test first. The result shows that the three methods of assessment fund performance is aligned and has an impact on mutual fund market value. The better the performance of a mutual fund tend to improve financial reporting conducted by the investment manager delivered to investors and potential investors, the market value of mutual funds will be higher and this will trigger potential investors to invest their funds into mutual funds and will be profitable. Keywords: IFR, Internet Financial Reporting, Mutual Funds,Mutual Fund Market Value, Mutual Fund Performance.